Political influence, firm performance and survival - Vladimir Sokolov; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
We examine how regional-level political influence affects firm financial performance and survival. Combining representative survey data on mid-sized manufacturing firms in Russia with official registry data, we find that politically influential firms exhibit higher profitability and retain larger financial investments than non-influential firms. At the same time, we find no association between regional political influence and access to bank lending. Most importantly, our empirical analysis suggests that the benefits of influence may be transient. Influential firms experienced significantly lower growth during our 2004–2010 sample period than non-influential firms. Moreover, influential firms had a significantly higher probability of going bankrupt after the 2008 global financial crisis than non-influential firms.
URN:NBN:fi:bof-201612271553
Keywords: D22; D72; G38; 330